The Association of OLFM4 with the Progression and Cisplatin Resistance of Head and Neck Squamous Carcinoma - Xinlu He; Xi Yao; Keling Pang; Xulin Chen; Zhengbo Wei; Ying Xie (Current Oncology)
Head and neck squamous cell carcinoma (HNSCC) is a highly prevalent malignant tumor globally with a poor prognosis. Despite continuous advancements in treatment modalities, the molecular mechanisms underlying its progression and chemotherapy resistance remain unclear. In previous studies, cisplatin drug induction was performed on HNSCC patient-derived tumor organoids (HNSCC-PDOs), successfully establishing a cisplatin-resistant organoid model (HNSCC-PDOcisR). This study conducted RNA sequencing on cisplatin-resistant HNSCC-PDOcisR and their parental PDOs. Bioinformatic analysis revealed that the oncoprotein olfactomedin 4 (OLFM4) was significantly upregulated in the drug-resistant model. Combined analysis of TCGA and CPTAC databases demonstrated that OLFM4 expression correlates with poor clinical prognosis in HNSCC. In vitro cellular experiments verified that OLFM4 overexpression significantly enhanced HNSCC cell proliferation, migration, and invasion capabilities (p < 0.05), while OLFM4 knockdown inhibited these phenotypes. Additionally, OLFM4 was found to mediate cisplatin resistance by regulating levels of reactive oxygen species (ROS), malondialdehyde (MDA), and ferrous ions (Fe2⁺), suppressing cisplatin-induced oxidative stress and ferroptosis while maintaining mitochondrial membrane potential. This study confirms that OLFM4 enhances tumor cell proliferation, migration, and resistance to cisplatin-induced cell death, thereby promoting HNSCC progression. These findings suggest OLFM4 may serve as a prognostic biomarker for HNSCC and a potential therapeutic target to reverse cisplatin resistance in HNSCC.